Fenologia da vegetação em áreas de Areias Brancas no Parque Nacional Serra de Itabaiana, Sergipe, Brasil - Machado, Wedna de Jesus (2018)
The phenological studies contribute to the understanding of species regeneration and reproduction, temporal organization of resources within communities, interactions and coevolution between plants and animals. The objective of this work was to analyze the phenological behavior of the species that make up the vegetation of white sands in the Serra de Itabaiana National Park, Northeastern Brazil, relate it to the climatic variables (precipitation and temperature), and to characterize the fruits types of these species to determine diaspore dispersion syndromes. To record the phonological activity, biweekly expeditions carried out (September/2015 to August/2017). It was verified the occurrence of 115 species and 13 types of fruits, the most frequent: capsule (31.3%), drupoid (16.5%) and bacoid (15.7%). The main dispersion syndrome was zoochory (46.1%), followed by anemochory (27.8%), and autochory (26.1%). For the shrub-tree component, most of the species presented semi-deciduous phenological strategy (73.3%), with continuous foliar activity. Flowering and fruiting recorded peaks of intensity in the dry and dry-rain seasons, respectively. As for the herbaceous-subshrub component, most of the species also presented continuous foliar activity, and flowering and fruiting with intensity peaks at the end of the rainy season and beginning of the dry season, respectively. It was observed a predominance of zoochoric species (80.0%) for the shrub-tree component, and of autochoric species (39.4%) for the herbaceous-subshrub component, as well as different fruiting patterns between biotic and abiotic syndromes, with greater activity in the rainy and dry seasons, respectively, for both components of the vegetation. The temperature was the climatic variable that most correlated with the phenological events of the shrub-trees component, and the precipitation, with the phenological events of herbaceous-subshrubs component, suggesting that rainfall may be a limiting factor for most species of this component. Knowledge of phenology is fundamental to understanding the dynamics of plant communities.